In-hospital length of stay after major surgical oncological procedures. Issue 7 (July 2018) - Nazzani, Sebastiano; Preisser, Felix; Mazzone, Elio; Tian, Zhe; Mistretta, Francesco A.; Shariat, Shahrokh F.; Saad, Fred; Graefen, Markus; Tilki, Derya; Montanari, Emanuele; Luzzago, Stefano; Briganti, Alberto; et al.
Abstract: Background and objectives: Enhanced recovery after surgery protocols (ERAS) have been developed and implemented as of 2001. However, no previous analyses targeted length of stay (LOS) changes over time after major surgical oncological procedures (MSOPs). Methods: Between 2003 and 2013, we retrospectively identified patients, who underwent prostatectomy, colectomy, cystectomy, mastectomy, gastrectomy, hysterectomy, nephrectomy, oophorectomy, lung resection or pancreatectomy within the Nationwide Inpatient Sample. A total of 3 431 602 assessable patients were identified. We examined temporal trends of LOS after ten MSOPs, as well as LOS determinants and the impact of LOS on total hospital charges (THCGs). Univariable and multivariable linear, log-linear, logistic (MLR) and Poisson regression (MPR) analyses were used. Results: Mean and median LOS were respectively 6 and 4 days (IQR 2–7). During the study span, LOS decreased [Estimated annual percentage change (EAPC): −1.89%, p = 0.0002]. Of the ten examined MSOPs, nine showed a decrease that ranged from −4.47% in prostatectomy to −0.7% in mastectomy. Conversely, no decrease in LOS was recorded for colectomy (EAPC:+0.37, p = 0.015). In MPR analyses, robotic [Relative risk (RR):0.68, p = 0.0003] and laparoscopic (RR: 0.90, p < 0.0001) surgical approaches were associated with shorter LOS. LOS was directly related to THCGs. Conclusions: Since the implementation of ERAS protocols, LOS has decreased for nine out of ten MSOPs in a significant fashion. Although these gains may appear marginal on an annual basis, their cumulative effect, over the study span, ranges for 7.7%–49.2%, which can hardly be interpreted as marginal. LOS decrease directly translates in THCGs savings.